Primary anterior perineal hernia: A case report and review of the literature. Issue 4 (1st April 2020) - Watanobe, Ikuo; Miyano, Shozo; Machida, Michio; Sugo, Hiroyuki
Abstract: Perineal hernia is a type of pelvic floor hernia and an extremely rare pathologic state. Perineal hernias can be classified into anterior and posterior types according to their positional relationship to the superficial transverse perineal muscle. A 49‐year‐old woman presented with bulging of the right labium major while standing. Standing external ultrasonography revealed a mass in the bulge, which could not be identified by transvaginal ultrasonography, CT, or MRI. Although hernia content could not be identified preoperatively, the patient was given a diagnosis of primary perineal hernia and underwent laparoscopic repair. Symptoms resolved postoperatively, and no sign of relapse has been noted for 8 months postoperatively. Here, we report the case details and review previous case reports.